Standardized national medication plan : The pilot projects MetropolMediplan 2016, model region Erfurt, and PRIMA - Dormann, Harald; Maas, Renke; Eickhoff, Christiane; Mueller, Uta; Schulz, Martin; Brell, Danny; Thuermann, Petra A. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2018)
Since 1 October 2016, all legally insured persons are entitled to a nationwide medication plan (BMP) under certain conditions (according to § 31a SGB V, E-Health Law). The catalogue of measures of the 3rd Action Plan 2013-2015 for the improvement of drug therapy safety (AMTS) provided for the testing of a medication plan in practice, including its acceptance and practicability in three model projects. These three projects - MetropolMediplan 2016, Erfurt, and PRIMA - are presented and recommendations are derived on the basis of the collected findings. Overall, the BMP was welcomed by the participating patients in all projects and led to an increase in satisfaction and an improvement in competence with regard to medication. Both doctors and pharmacists rated the interdisciplinary cooperation via the medium BMP very positively. The high effort and lack of technical infrastructure without electronic availability of the last current version of a BMP of the individual patient was perceived as negative. An original data comparison of the BMP data with the drugs actually taken in the MetropolMediplan 2016 project showed that only 36% of the patients were in agreement with the BMP and the drugs presently taken. The paper version of the BMP has therefore not yet been able to solve the problem of the timeliness and completeness of the medication. In addition to various proposals for the further development of BMP, all parties involved require the BMP to be available electronically across all sectors. The BMP should therefore be an important instrument for improving AMTS in the future.
EVALuna2:34649